Assessment of the Economic Aspects of Trap Net Fisheries Business in the Waters of Segeri District, Pangkep Regency - Ihsan, Ihsan; Jamal, Muhammad; Asbar, Asbar; Kafi, Ahmad Taufiq (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Pangkep Regency has abundant potential resources, which are utilized by various fishing gears including trap net fisheries. This study aims to determine the economic value of the trap net fishery business. The research was carried out in October-November 2020, the research location was in the coastal area of Sigeri District, Pangkep Regency. The research method was carried out by direct survey in the field. The data collected consists of primary data and secondary data. The primary data includes investment costs, maintenance costs, operational costs and catch production during the research. Secondary data includes Pangkep data in 2020 figures. The results show that the economic value of the trap net fishing business is declared feasible, with an average RC ratio value of 1.5, meaning that every time it costs Rp. 1 then the fishermen get an income of Rp. 0.5. The trap net fishing business contributes to a better and more profitable economy for fishermen who operate trap net fishing gear.